2006
DOI: 10.1002/14651858.cd000553.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Portosystemic shunts versus endoscopic therapy for variceal rebleeding in patients with cirrhosis

Abstract: Portosystemic shunts versus endoscopic therapy for variceal rebleeding in patients with cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 70 publications
2
19
0
1
Order By: Relevance
“…Our findings are comparable to the results of a previous meta-analysis by Khan et al 37 that compared the efficacy of surgical shunts (total surgical stunts: distal spleno-renal shunts (DSRS) or TIPS) and endoscopic therapy (sclerotherapy and/or banding) for the prevention of rebleeding in patients with cirrhosis 37. Their study included 22 trials with 1409 patients.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are comparable to the results of a previous meta-analysis by Khan et al 37 that compared the efficacy of surgical shunts (total surgical stunts: distal spleno-renal shunts (DSRS) or TIPS) and endoscopic therapy (sclerotherapy and/or banding) for the prevention of rebleeding in patients with cirrhosis 37. Their study included 22 trials with 1409 patients.…”
Section: Discussionsupporting
confidence: 88%
“…TIPS is rapidly becoming a front line approach for secondary prophylaxis and should be considered especially among patients with high risks of treatment failure with EVBL. 29-31 In its absence, a combination of EVBL and nonselective beta blockers constitutes the standard of care of prevention of variceal rebleeding. Multiple trials have evaluated and demonstrated that combination therapy is superior to either EVBL alone or pharmacological therapy alone for secondary prophylaxis.…”
Section: Specific Therapies For Esophageal Variceal Bleedingmentioning
confidence: 99%
“…The guideline has been piloted among target users Rigor of development (items [8][9][10][11][12][13][14] 8. The average score was 78.1 (median 82.3, range 46-100).…”
Section: Scope and Purpose (Domain 1)mentioning
confidence: 99%
“…Endoscopic methods [6][7][8], vasoactive drugs [9][10][11], radiological interventions [12], and surgical procedures [13,14] improve the prognosis of acute bleeding episodes, with a decrease in immediate mortality due to bleeding. However, the short-term and medium-term effectiveness of these interventions is still being evaluated [15,16].…”
Section: Introductionmentioning
confidence: 99%